UNCERTAINTY REDUCTION STRATEGIES FOR PARENTS OF DAY CARE SERVICE USERS - Rahmadiana Rahmadiana; Salim Salim (Journal of Digital Media Communication, 2023)
Interpersonal communication typically involves two individuals engaging in dialogue, whether acquainted or unfamiliar. However, when individuals engage in conversation after a recent encounter, there is a tendency for uncertainty to arise. Uncertainty and anxiety surface when one lacks information about their conversational partner, compelling them to employ strategies to reduce this uncertainty. This study aims to elucidate the types of uncertainty experienced by parents utilizing the services of "Teman Kecil" Day Care for their children and explore their strategies for alleviating uncertainty using the Uncertainty Reduction Theory proposed by Berger and Calabrese. Employing a case study approach, the researchers gathered qualitative data through in-depth interviews with parents and caregivers at "Teman Kecil" Day Care. The findings reveal that parents experience cognitive uncertainty, wherein they feel unsure about the situations their children will encounter while in the care of "Teman Kecil" Day Care. To mitigate this uncertainty, parents actively employ strategies such as conducting surveys through social media platforms like Instagram, consulting Google Reviews, and seeking advice from peers with prior daycare experiences. Additionally, parents passively employ strategies by observing the caregivers at "Teman Kecil" Day Care. Lastly, parents employ interactive strategies to comprehensively understand the forthcoming situations, engaging in face-to-face communication with caregivers to acquire the necessary information.